Productivity of Advanced Clinical Practitioners in Emergency Medicine: A 1-year dual-centre retrospective analysis. (July 2020) - Fenwick, Rob; Soanes, Kirsti; Raven, David; Park, Caroline; Jones, Ellen
Highlights: ACP roles are increasingly prevalent in UK Emergency Medicine. There is currently little evidence evaluating their overall impact. This study of ACP productivity demonstrated rates of 1.03–1.53 PPH. There is a significant correlation between years qualified as an ACP and PPH. These results should be applied in the context of wider evaluation methods. Abstract: Background: The ACP role is relatively new in Emergency Medicine (EM) nationally (RCEM, 2017). This work sought to establish the productivity of EM ACPs within our service, to enable evidence-based workforce planning and national benchmarking of this aspect of the role. Methodology: Data from 1st January 2018–31st December 2018 was retrospectively collected from two hospitals in the United Kingdom (UK) via electronic patient records. In addition to the number of patients seen by ACPs (attending), the number of patients who were seen by an ACP as a senior review (SR) was collected. The productivity was mapped to ACP experience, with patient acuity and disposal reported. Results: In the study period 239, 951 patients were seen in the Emergency Departments (EDs) of the two study hospitals. Overall 20, 442 (8.5%) patients received care from an ACP. Mean productivity was 1.03 patients per hour (attending) and 1.53 patients per hour (attending and senior review). Discussion: EM ACPs form part of the RCEM future workforce strategy to overcome some of the contemporary challenges in EM (Hassan, 2018). To our knowledge, this is the first study which has examined and reported the productivity of ACPs in UK EM. Conclusion: This paper sets a national benchmark for other EDs by reporting ACP productivity and contributes to the evidence by reporting productivity in other clinician groups. The data presented may be helpful in future national workforce planning for UK EDs.